A Decade of Advances in Military Trauma Care. (June 2014) - Glassberg, E.; Nadler, R.; Erlich, T.; Klien, Y.; Kreiss, Y.; Kluger, Y.
Background: While combat casualty care shares many key concepts with civilian trauma systems, its unique features mandate certain practices that are distinct from the civilian ones. Methods: This is a review of the most current literature on combat casualty care, based on computer database searches for studies on combat casualty care and military medicine. Studies were selected for inclusion in this review based on their relevance and contribution. Results: Over the last decade, meticulous, international data collection and research efforts have led to significant improvements in military trauma care. Combat medicine has focused on the causes of preventable deaths and targeted on bleeding control and resuscitation strategies, as well as improved evacuation. En route care and forward surgical interventions have resulted in unprecedented low fatality rates and the saving of more lives. Conclusion: This overview of the developments in combat casualty care in recent years emphasizes medical practices that are characteristic of combat medicine, yet with the potential to save lives in other scenarios, as well.